2021
DOI: 10.3390/nu13061987
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Regulates Postoperative Serum Levels of PD-L1 in Patients with Digestive Tract Cancer and Improves Survivals in the Highest Quintile of PD-L1: A Post Hoc Analysis of the AMATERASU Randomized Controlled Trial

Abstract: Because vitamin D responsive elements have been found to be located in the PD-L1 gene, vitamin D supplementation was hypothesized to regulate serum PD-L1 levels and thus alter survival time of cancer patients. A post hoc analysis of the AMATERASU randomized, double-blind, placebo-controlled trial of postoperative vitamin D3 supplementation (2000 IU/day) in 417 patients with stage I to stage III digestive tract cancer from the esophagus to the rectum was conducted. Postoperative serum PD-L1 levels were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Programmed death-ligand 1 (PD-L1) as an anticancer immunity counter expression of cancer cells, was found to be upregulated. PD-L1 was measured through ELISA, divided into five quintiles; and vit D supplementation was found to significantly reduce the risk of relapses and death to approximately 30% of the highest quantile of serum PD-L1 ( 89 ).…”
Section: Antioxidants Acting As Protumorigenicmentioning
confidence: 99%
“…Programmed death-ligand 1 (PD-L1) as an anticancer immunity counter expression of cancer cells, was found to be upregulated. PD-L1 was measured through ELISA, divided into five quintiles; and vit D supplementation was found to significantly reduce the risk of relapses and death to approximately 30% of the highest quantile of serum PD-L1 ( 89 ).…”
Section: Antioxidants Acting As Protumorigenicmentioning
confidence: 99%
“…One RCT found mixed results for vitamin D supplementation with 200 IU/day in patients with digestive-tract cancer, post-curative surgery [ 55 ]. The study found that the effect of supplementation depended on the levels of serum Programmed Death Ligand 1 (PD-L1), a regulatory molecule expressed in T cells with immunosuppressive function [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…One RCT found mixed results for vitamin D supplementation with 200 IU/day in patients with digestive-tract cancer, post-curative surgery [ 55 ]. The study found that the effect of supplementation depended on the levels of serum Programmed Death Ligand 1 (PD-L1), a regulatory molecule expressed in T cells with immunosuppressive function [ 55 ]. Since PD-L1 is associated with a poorer cancer prognosis in various types of cancer (gastric cancer, small cell lung cancer, pancreatic cancer, breast cancer) [ 83 , 84 , 85 , 86 ], for those patients in the lowest PD-L1 concentration quintile, vitamin D supplementation seemed to have a detrimental effect by upregulating serum PD-L1 levels; however, for those in the highest quintile, vitamin D was beneficial and downregulated serum PD-L1 levels [ 55 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is still unclear why CD4 + , CD8 + T lymphocytes decrease in vitamin D deficiency and how these lymphocytes increase with vitamin D supplementation. However, in a recent study, Morita et al ( 2021 ) reported that vitamin D supplementation may have a bimodal function of increasing serum PD-L1 when serum PD-L1 levels are very low and decreasing serum PD-L1 levels when serum PD-L1 levels are very high. Presumably, vitamin D could increase the number of T lymphocytes by eliminating the suppressive effect of the PD-1 PD-L1 pathway on T lymphocytes.…”
Section: Covid-19 Pd-1/pd-l1 Signaling and Vitamin Dmentioning
confidence: 98%